MGNREGA And Water Management: Sustainability Issues Of Built Forms In Rural India - Chakraborty, Banhi; Das, Sutapa (Penerbit Universiti Sains Malaysia, 2014)
Compared to urban sustainability, rural sustainability has traditionally received inadequate attention, especially in developing countries such as India. Because of their symbiotic relation with the local climate and landforms, vernacular structures of rural India are said to be inherently sustainable. However, since 2005, substantial amounts of intervention brought about by the Mahatma Gandhi National Rural Employment Generation Act (MGNREGA) have changed this situation. India's rural landscape is now intersected with numerous built forms, such as road networks, water management systems, and land development. Unfortunately, the MGNREGA's goal of addressing the substantial void that characterised rural areas and bringing about a sustainable future through the generation of the multiplier effect have not been achieved in most cases. This study was conducted to investigate the reasons for this unexpected outcome. Water management, constituting the major thrust of the MGNREGA, was examined for two purposively selected areas with distinctively different physio-climatological variations at the micro level from the state of West Bengal. The data from the MGNREGA website and from field investigations show a short-term benefit, whereas sustainability issues on a long-term basis remain a concern. Straightjacketed norms for scheme implementation ignoring physical heterogeneity across the country appear to be a major cause. Reframing and customisation of construction specifications are recommended as a solution.